Factors for cognitive impairment in adult epileptic patients. Issue 1 (21st December 2019) - Wang, Lei; Chen, Shenggen; Liu, Changyun; Lin, Wanhui; Huang, Huapin
Abstract: Objective: To analyze factors for cognitive impairment in epileptic patients. Methods: A total of 257 epileptic patients completed clinical memory scale (CMS) and 70 of them were further surveyed with mini‐mental state examination (MMSE), Montreal cognitive assessment (MoCA), digital symbol test (DSy), verbal fluency test, digit span test (DSp), Hamilton anxiety scale (HAMA) and Hamilton depression scale (HAMD). Monadic linear related analysis and multiple stepwise regression analysis were performed to evaluate the potential factors for cognitive impairment. Results: Educational level was correlated with scores of cognitive tests ( p < .01), with a difference between the junior high school group and senior high school group ( p < .01 or p < .05). Seizure frequency was negatively correlated with CMS scores ( p < .01), with a difference between the group with a seizure frequency of less than once a year and other groups ( p < .01). The kind of antiepileptic drugs (AEDs) was negatively correlated with CMS scores ( p < .01), with a difference between the single‐drug group and the group taking more than two kinds of AEDs ( p < .01). Depression scores were negatively correlated with MMSE, MoCA, DSy, DSp ( p < .01 or p < .05), disease duration negatively with DSy ( p < .01), and age negatively with MoCA ( p < .05). Seizure type was correlated with DSy, and general seizure fared worse in the tests than other seizure types ( p < .05). Conclusion: Educational level, seizure frequency, kinds of AEDs and depression can affect the cognitive function of epileptic patients. High educational level, good seizure control, single‐drug treatment and healthy psychological state are protective factors for cognitive function of epileptic patients. Abstract : Educational level, seizure frequency, kinds of antiepileptic drugs, and depression can affect the cognitive function of epileptic patients. High educational level, good seizure control, single‐drug treatment, and healthy psychological state are protective factors for cognitive function of epileptic patients. These findings provide a new strategy for avoiding cognitive impairment in epileptic patients.